Mensajes de odio hacia la comunidad LGTBIQ+: análisis de los perfiles de Instagram de la prensa española durante la "Semana del Orgullo". - Valerio, Lizette Martínez (Revista Latina de Comunicación Social, 2022)
Introduction: Some experts agree on the fundamental role that social networks have in the increase in hate crimes in recent years, especially among the younger population. Aware of this reality, these platforms continuously take measures to prevent hate speech from spreading through the Internet. However, the collaboration of the rest of those involved in the communication process is also necessary. One of them is the media. This research focused on analyzing the comments made on the Instagram posts of the main Spanish newspapers of national circulation (El País, El Mundo, ABC, La Vanguardia and 20Minutos) related to what is known as "Pride Week". Methodology: The methodology used was the quantitative and empirical content analysis of all the comments made in the publications (N = 20) of the Instagram accounts belonging to those newspapers. Results: The corpus obtained turned out to be 6,013 comments: 41.8% classified as "other", 32.6% "in favor", 16% "critics", 4.9% "teasing", 3.1% "contempt", 1.5% "insults" and 0.1% "threats". Discussion: The results coincide with other studies in which the filters established by Instagram reduce hate speech on this network, unlike others such as Twitter. Conclusions: Most of the messages regarding the LGTBIQ + group are in favor, and, although most of the messages against can be classified as critics, there is a small percentage of messages that can be considered hate speech.